2010
DOI: 10.1063/1.3480016
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on emission characteristics of the pongamia biodiesel–diesel blend fuelled twin cylinder compression ignition direct injection engine using exhaust gas recirculation methodology and dimethyl carbonate as additive

Abstract: Experiments were carried out on a twin cylinder direct injection compression ignition engine using pongamia biodiesel–diesel blend as fuel with exhaust gas recirculation (EGR) and dimethyl carbonate (DMC) as additive. The experimental results showed that pongamia biodiesel–diesel blend fuelled engine with EGR and DMC can simultaneously reduce smoke and nitric oxide (NOx) emission. The NOx emission was reduced by about 17.68% for 10% of EGR introduction and about 13.55% increase in smoke emission. When dimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…6 Pandian et al claimed that the addition of DMC along with exhaust gas recirculation made the engine emit less smoke and lower NO x , CO, and hydrocarbon emissions. 358…”
Section: Fuel Additivesmentioning
confidence: 99%
“…6 Pandian et al claimed that the addition of DMC along with exhaust gas recirculation made the engine emit less smoke and lower NO x , CO, and hydrocarbon emissions. 358…”
Section: Fuel Additivesmentioning
confidence: 99%
“…The advantage of early injection is associated with homogeneous mixtures. This is particularly important, since there is not enough time for diesel engines to obtain a homogenous gas and fuel mixture [21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…The RNG kepsilon is generally preferred for internal combustion engine simulations because of its better calibration than the standard k-epsilon turbulence model. The RNG k-ε and Standard k-ε turbulence models are generally preferred if the Reynolds number is high [23].…”
Section: Resultsmentioning
confidence: 99%
“…Also found that the reduction of Hydrocarbon, carbon monoxide and oxides of nitrogen emission have been decreased [6,7]. The EGR technique is the most efficient method to lower the oxides of nitrogen from the diesel engine emission, the salient feature of using the EGR technique is to reduce flame temperature and oxygen concentration in the engine combustion [8]. The higher drop of NOx was essentially due to lower combustion chamber flame temperature and less available oxygen content of using Jatropha biodiesel and EGR technique [9].…”
Section: Introductionmentioning
confidence: 99%